What are the demographic consequences of a seed bank stage for columnar cacti? - Arroyo-Cosultchi, G; Golubov, J; Mandujano, MC; Salguero-Gomez, R; Martinez, AJ (Wiley, 2021)
The dynamics of plant populations are often limited by the early stages in their life cycles. However, information regarding seed bank dynamics and how these may influence the whole life cycle of plant species is remarkably scarce or not considered explicitly. This lack of knowledge is due mainly to the challenges in quantifying seed vital rates. Studies of arid land plant species have historically been focused on the drivers of sporadic recruitment. However, little attention has been given to the demographic consequences of early developmental stages, and how seed banks affect their dynamics. Here, we evaluate the effects of seed bank survival and seedling recruitment vital rates on the population dynamics and viability of 12 columnar cacti species. Recent evidence suggests that cacti seeds may remain viable for the short-term. We assess how changes in the vital rates of these processes and the inclusion of a seed bank affect population growth rate (λ). We found that a seed bank in the examined matrix population models significantly increased λ as well as the vital rate elasticities of λ to growth and fecundity, whereas that of overall survival decreased. Our numerical simulations showed that seed survival had a more considerable effect on λ than seedling recruitment and establishment. We suggest that the seed bank may explain the structure and population dynamics. Thus, we reconsider that this early stage in demographic models will generate more informed decisions on the conservation and management of columnar cacti.